1980
DOI: 10.1901/jeab.1980.34-319
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Pecking and Timeout Under a Multiple Fixed‐ratio Schedule of Food Delivery

Abstract: Pigeons were trained to peck a key under a multiple fixed-ratio 25 fixed-ratio 175 schedule of food presentation. In the first condition, either a mirror or the opportunity to produce a 30-second timeout were available. In a second condition, mirror and timeout availability were reversed for the two groups. Following a return to the initial condition, mirror and timeout keys were presented together for all birds. Mirror and timeout responses occurred predominantly in the pause in the larger fixed-ratio compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…Because the birds pecked the escape key, Azrin concluded that schedules of positive reinforcement have aversive aspects. Other studies of FR schedules (Appel, 1963; Ator, 1980; Thompson, 1964, 1965), FI schedules (Brown & Flory, 1972; Cohen & Campagnoni, 1989), and progressive‐ratio schedules (Dardano, 1973, 1974) have confirmed escape responding during the period immediately following reinforcer delivery.…”
Section: Discussionmentioning
confidence: 88%
“…Because the birds pecked the escape key, Azrin concluded that schedules of positive reinforcement have aversive aspects. Other studies of FR schedules (Appel, 1963; Ator, 1980; Thompson, 1964, 1965), FI schedules (Brown & Flory, 1972; Cohen & Campagnoni, 1989), and progressive‐ratio schedules (Dardano, 1973, 1974) have confirmed escape responding during the period immediately following reinforcer delivery.…”
Section: Discussionmentioning
confidence: 88%
“…Alternatively, there may be aversive aspects of the fixed-ratio response requirements leading to increased levels of induced behavior. Numerous studies have demonstrated that pigeons or rats will respond to terminate or escape from stimuli associated with schedules of positive reinforcement (e.g., Appel, 1963;Ator, 1980;Azrin, 1961;Brown & Flory, 1972;Dardano, 1973;Dinsmoor, Lee, & Brown, 1986;Thompson, 1964) This escape behavior usually occurs in the early postreinforcement period, when the probability of reinforcement is low. Azrin et al (1966) and Hutchinson et al (1968) suggest that induced attack during ratio schedules may be a function of the aversive elements related to response number required for reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…For the FR schedule, the pause was measured as the time between delivery of the previous reinforcer and completion of the fifth response within the next ratio. The procedure of using the fifth response rather than the first incorporated most of the drinking bouts (87%) into the pause, and it discounted instances in which the sustained part of the ratio run was preceded by a few spaced responses (for a similar approach, see Ator, 1980;Capehart, Eckerman, Guilkey, & Shull, 1980). The same procedure was used for the VR schedule except that pauses preceding ratios with a single response were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%